2004
DOI: 10.1542/peds.2004-0085
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Adherence to Highly Active Antiretroviral Therapy Into Children's Daily Lives: A Qualitative Study

Abstract: ABSTRACT.Objective. To acquire a deeper understanding of factors that influence adherence to highly active antiretroviral therapy (HAART) in a pediatric population.Methods. We performed a qualitative study of adherence in children who receive HAART in a Belgian pediatric acquired immune deficiency syndrome referral center. Eleven primary caregivers were interviewed to assess their child's adherence and influencing factors. The interview guidelines were developed on the basis of an extensive literature review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
(26 reference statements)
3
46
0
3
Order By: Relevance
“…It is uncommon for families to disclose a child's HIV status to most people outside of the immediate family; thus, even when families have effective strategies for remembering doses, children may miss doses due to concerns that others will inadvertently learn about the child's HIV status. 28,53 Yet stigma does not explain the lack of relationship between memory strategies and adherence in this study, given that only 2% of caregivers reported that nonprivacy was a barrier.…”
Section: Said They Used No Strategiesmentioning
confidence: 65%
“…It is uncommon for families to disclose a child's HIV status to most people outside of the immediate family; thus, even when families have effective strategies for remembering doses, children may miss doses due to concerns that others will inadvertently learn about the child's HIV status. 28,53 Yet stigma does not explain the lack of relationship between memory strategies and adherence in this study, given that only 2% of caregivers reported that nonprivacy was a barrier.…”
Section: Said They Used No Strategiesmentioning
confidence: 65%
“…Hammami et al, 49 however, presented findings that confirmed the information-motivation-behavioral skills model. 50 Specifically, in their qualitative study of 11 caregivers of HIV-positive children in Belgium, adherence was associated with (1) knowledge of the disease and its treatment; (2) motivation or willingness to adhere (which depended on the acceptance of the HIV diagnosis, the emotional quality of the mother-child relationship, and the recognition of future prospects); and (3) the capacity or ability to adhere (which depended on having the necessary cognitive and technical skills to follow a medication scheme, perceived self-efficacy, and problemsolving capacity).…”
Section: Factors Related To Adherencementioning
confidence: 91%
“…This technique does not use pre-set questions, but is shaped by a defined set of topics. The topics (Table 1) were informed by a literature review of published studies relevant to factors influencing adherence in children (Bikaako-Kajura et al, 2006;Boni et al, 2000;Elise et al, 2005;Giacomet et al, 2003;Gibb et al, 2003;Goode et al, 2003;Hammami et al, 2004;Marhefka et al, 2006;Martin et al, 2007;Mellins et al, 2004;Nicholson et al, 2006;Pontali et al, 2001;Reddington et al, 2000;Temple et al, 2001;Williams et al 2006). All interviews were conducted by the principal investigator who had no role in the clinical care provided at the organisation.…”
Section: Methodsmentioning
confidence: 99%
“…Sustaining good adherence to ART in children is difficult as it is influenced by several factors including child behaviour, tolerability of medications, access to health services, HIV status of caregivers and their attitudes and beliefs (Bikaako-Kajura et al, 2006;Boni, Pontali, De Gol, Pedemonte & Bassetti, 2000;Elise et al, 2005;Giacomet et al, 2003;Gibb et al, 2003;Goode, McMaugh, Crisp, Wales & Ziegler, 2003;Hammami et al, 2004;Marhefka, Tepper, Brown, & Farley, 2006;Martin et al, 2007;Mellins, Brackis-Cott, Dolezal & Abrams, 2004;Nicholson et al, 2006;Pontali et al, 2001;Reddington et al, 2000;Temple, Koranyi, & Nahata, 2001;Williams et al 2006). Nonadherence leading to anti-viral resistance necessitates the use of more expensive and often more toxic second or third line drugs with disastrous implications at both individual and population levels (Mullen et al, 2002).…”
Section: Manuscript Introductionmentioning
confidence: 99%